Hyperglycemia and bladder cancer prognosis in a Finnish population-based cohort - Lauri Vuoristo; Antti Poyhonen; Silja M. Vuorlaakso; Andres Kotsar; Teuvo L.J. Tammela; Teemu J. Murtola (PLoS ONE, 2025)
Background Diabetes might increase risk of bladder cancer (BCa) incidence and bladder cancer specific death. Objective To assess the potential association between diabetes and prognosis of BCa. Design, setting and participants Register-based cohort study included 14,638 participants with BCa diagnosed in Finland during 1995–2012. Three databases were used to obtain information on BCa, diabetes and comorbidities. Hyperglycemia was determined by blood glucose or HbA1c. The role of antidiabetic medication use was also assessed. Outcome measurements and statistical analysis Associations between diabetes and BCa-specific and overall mortality were evaluated using multivariable Cox regression models. Results and limitation During median follow-up of 4.3 years after BCa diagnosis 3,582 (24.5%) participants died of BCa. Diabetic post-diagnostic blood glucose level was associated with worse BCa-specific HR 1.58 (1.10–2.28) and overall survival HR 1.50 (1.20–1.89). The risk increase was slightly lower among hyperglycemic DM medication users (HR 1.43 (0,68–3.02) than non-users HR 1.80 (1.13–2.85). The main limitation of this study was insufficient information on tobacco smoking. Conclusions Diabetes and diabetic glycemic status were associated with increased risk of both overall and BCa-specific death. Patient summary In a Finnish population-based cohort study, diabetic bladder cancer patients had worse prognosis compared to non-diabetics. This was observed in both genders.